USING INSTAGRAM CAPTION TO IMPROVE VOCABULARY MASTERY OF EIGHTH GRADE STUDENTS OF SMPN 19 PALU - Artanti, Ni Luh Rani; Thamrin, Nur Sehang; Anggreni, Afrillia (e-Journal of ELTS (English Language Teaching Society), 2024)
The objective of this research is to find out whether Instagram caption can improve the vocabulary mastery of eighth grade students of SMPN 19 Palu or not. This research used quasi experimental research design. The population of this research was the eighth-grade students of SMPN 19 Palu which is consisted of 98 students. The sample of the research consisted of two groups which were selected through simple random sampling, the groups such as class B as the experimental group and class D as the control group. The researcher used tests to collect the data, the tests consisted of the pre-test and the post-test. The result of the test showed that the mean score of the pre-test of the experimental group was 20.62, while the mean score of control group was 20.40. Then, the mean score of the post-test of experimental group was 79.96, while the mean score of control group was 68.92. The value of t-counted (3.01) was higher than the value of t-table (2.0116), it means that the hypothesis was accepted. Based on the result, it can be concluded that using Instagram caption can improve vocabulary mastery of the eighth-grade students of SMPN 19 Palu. The implication of the findings that the teachers should use instructional media that can improve students' motivation to learn new words by making sentence while teaching vocabulary mastery using Instagram caption